Pru p 3 sensitization in children with allergy to Parietaria pollens - Ciprandi, Giorgio; Del Barba, Paolo; Silvestri, Michela; Barberi, Salvatore; Tosca, Maria Angela (Acta Biomedica Atenei Parmensis, 2019)
Background: Pru p 3 is the major allergen of the peach and belongs to the LTP family. Pru p 3 sensitization has been associated with severe allergic symptoms after eating LTP-containing foods. However, a previous experience partially downsized the potential danger of Pru p 3 sensitization in a group of adult rhinitics. This study aimed to evaluate the real impact of Pru p 3 sensitization in children in a real-world setting. Methods: 82 consecutive paediatric patients (55 males and 27 females, mean age 8.19±4.23 years) with allergic rhinitis due to Parietaria pollen allergy and sensitization to Pru p 3, documented by ISAC test, were evaluated. Serum IgE was measured by ImmunoCap method. Allergic symptoms occurring after ingesting LTP-containing foods were considered and scored as oral allergy syndrome, food allergy, and anaphylaxis. Results: About one-quarter of Pru p 3-sensitized children reported anaphylaxis after ingesting LTP-containing foods, about half reported food allergy or oral allergy syndrome. Only ¼ was merely sensitized. Conclusions: Pru p 3 sensitization deserves careful attention in children contrary to what might occur in adult patients. It could depend on the age and the serum IgE level. Thus, Pru p 3 sensitization should be adequately interepreted and managed in clinical practice.